The type la supernova rate at z ≈ 0.5 from the supernova legacy survey - Neill, J; Sullivan, M; Balam, D; Pritchet, C; Howell, D; Perrett, K; Astier, P; Aubourg, E; Basa, S; Carlberg, R; Conley, A; Fabbro, S; et al. (2006)
We present a measurement of the distant Type la supernova (SN Ia) rate derived from the first 2 yr of the Canada-France-Hawaii Telescope Supernova Legacy Survey. We observed four 1° × 1° fields with a typical temporal frequency of (Δt) ∼ 4 observer-frame days over time spans of 158-211 days per season for each field, with breaks during the full Moon. We used 8-10 m class telescopes for spectroscopic follow-up to confirm our candidates and determine their redshifts. Our starting sample consists of 73 spectroscopically verified SNe la in the redshift range 0.2 < z < 0.6. We derive a volumetric SN Ia rate of r V(〈z〉 = 0.47) = [0.42 0.090.13(syst.) ± 0.06(stat.)] × 10 -4 yr -1 Mpc 3, assuming h = 0.7, Ω m -0.3, and a flat cosmology. Using recently published galaxy luminosity functions derived in our redshift range, we derive a SN Ia rate per unit luminosity of r L(〈z〉 = 0.47) = 0.154 -0.0330.048(syst.) 0.0310.039(stat.) SN units. Using our rate alone, we place an upper limit on the component of SN la production that tracks the cosmic star formation history of 1 SN la per 10 3 M ⊙ of stars formed. Our rate and other rates from surveys using spectroscopic sample confirmation display only a modest evolution out to z = 0.55. © 2006. The American Astronomical Society. All rights reserved.